Self-derivation through memory integration: A model for accumulation of semantic knowledge. (April 2020) - Bauer, Patricia J.; Esposito, Alena G.; Daly, James J.
Abstract: Semantic knowledge accumulates through explicit means and productive processes (e.g., analogy). These means work in concert when information explicitly acquired in separate episodes is integrated, and the integrated representation is used to self-derive new knowledge. We tested whether (a) self-derivation through memory integration extends beyond general information to science content, (b) self-derived information is retained, and (c) details of explicit learning episodes are retained. Testing was in second-grade classrooms (children 7–9 years). Children self-derived new knowledge; performance did not differ for general knowledge (Experiment 1) and science curriculum facts (Experiment 2). In Experiment 1, children retained self-derived knowledge over one week. In Experiment 2, children remembered details of the learning episodes that gave rise to self-derived knowledge; performance suggests that memory integration is dependent on explicit prompts. The findings support nomination of self-derivation through memory integration as a model for accumulation of semantic knowledge and inform the processes involved. Highlights: School children self-derive factual knowledge via memory integration in the classroom. Factual information newly self-derived in the classroom is retained over time. Self-derivation through memory integration extends to academic (science) content. Self-derivation through integration is a valid model of accrual of semantic knowledge.